Measuring the conditioned response: A comparison of pupillometry, skin conductance, and startle electromyography. (27th September 2018) - Leuchs, Laura; Schneider, Max; Spoormaker, Victor I.
Abstract: In human fear conditioning studies, different physiological readouts can be used to track conditioned responding during fear learning. Commonly employed readouts such as skin conductance responses (SCR) or startle responses have in recent years been complemented by pupillary readouts, but to date it is unknown how pupillary readouts relate to other measures of the conditioned response. To examine differences and communalities among pupil responses, SCR, and startle responses, we simultaneously recorded pupil diameter, skin conductance, and startle electromyography in 47 healthy subjects during fear acquisition, extinction, and a recall test on 2 consecutive days. The different measures correlated only weakly, displaying most prominent differences in their response patterns during fear acquisition. Whereas SCR and startle responses habituated, pupillary measures did not. Instead, they increased in response to fear conditioned stimuli and most closely followed ratings of unconditioned stimulus (US) expectancy. Moreover, we observed that startle‐induced pupil responses showed stimulus discrimination during fear acquisition, suggesting a fear potentiation of the auditory pupil reflex. We conclude that different physiological outcome measures of the conditioned response inform about different cognitive‐affective processes during fear learning, with pupil responses being least affected by physiological habituation and most closely following US expectancy.